2020
DOI: 10.1186/s12879-020-05480-y
|View full text |Cite
|
Sign up to set email alerts
|

New HIV diagnoses in patients with COVID-19: two case reports and a brief literature review

Abstract: Background COVID-19 is novel infectious disease with an evolving understanding of its epidemiology and clinical manifestations. Severe cases developed life-threatening complications, such as respiratory failure, shock, and multiple organs dysfunction. Immunocompromised patients often present atypical presentations of viral infected diseases. Case presentation We report newly diagnosed HIV infections in two patients with COVID-19 in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…One patient was screened after an employee's needlestick injury. New diagnosis of HIV at the time of COVID-19 diagnosis is not commonly reported at this time but brings forward the importance of considering additional diagnoses in patients with COVID-19 that are critically ill 22 and to emphasize the need for universal offering of HIV testing at the time of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…One patient was screened after an employee's needlestick injury. New diagnosis of HIV at the time of COVID-19 diagnosis is not commonly reported at this time but brings forward the importance of considering additional diagnoses in patients with COVID-19 that are critically ill 22 and to emphasize the need for universal offering of HIV testing at the time of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…However, sequential changes in blood counts were not documented in most studies on PLHIV with COVID-19. In this review, we found only three studies which reported changes in full blood counts [ 55 , 81 , 102 ]; however, all three reported cell counts within the normal range on admission and throughout hospitalization. While this may be the case, it is not unreasonable to expect that PLHIV will demonstrate a blood cell profile largely similar to that of non-HIV infected people as a response to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…77% of the patients in this series had at least one co-morbid condition, increasing their risk for worse outcomes. The first diagnosis of HIV in a patient with AIDS at the time of ICU admission for COVID-19 (also previously reported) [ 22 , 23 ] makes a compelling case for routine HIV screening on all patients hospitalized with severe or critical COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…It is unclear whether PWH have increased risk for secondary infections or other adverse events after the use of IL-6ri for severe COVID-19. There are few reports of PWH receiving IL-6ri for COVID-19 [ 22 , 23 ]. Here, we present 4 narrative case reports accompanied by a description of the outcomes of 18 patients with a diagnosis of HIV and PCR-confirmed COVID-19 treated with IL-6ri between April and June 2020.…”
Section: Introductionmentioning
confidence: 99%